IMPACT OF ELEVATED BLOOD GLUCOSE ON CORONARY ARTERY DISEASE SEVERITY AND OUTCOMES IN ST-ELEVATION MYOCARDIAL INFARCTION PATIENTS - Dr. Ahmad Usman; Dr. Ali Hassan; Dr. Iman Hussain; Dr. Aneeza Waris Hussain Rathore; Dr. Syed Ali Hadi Kirmani; Dr. Mohammad Imran Younus (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Diabetes mellitus (DM) is a known risk factor for the development and progression of coronary artery disease (CAD), particularly in acute conditions such as STEMI (ST-Elevation Myocardial Infarction). Elevated blood glucose levels, both random (RBG) and fasting (FBG), may worsen the severity of CAD and influence clinical outcomes following myocardial infarction (MI). This study aims to investigate the relationship between blood glucose levels, clinical outcomes, CAD severity, and the success of reperfusion therapy in STEMI patients. This prospective observational study was conducted at the Army Cardiac Hospital/CMH Lahore Medical College, Department of Cardiology, from August 2023 to March 2024. A total of 100 STEMI patients were enrolled and divided into two groups based on their RBG levels: non-hyperglycemic (RBG levels 200 mg/dL). Fasting blood glucose (FBG) was measured after 8 hours, and patients were further categorized into those with non-elevated FBG (126 mg/dL). Patients received either primary percutaneous coronary intervention (PCI) or pharmacoinvasive therapy as per the European Society of Cardiology (ESC) guidelines. The Gensini score was used to assess CAD severity, and major adverse cardiac events (MACE) were monitored during hospitalization. Patients with elevated FBG were older, had a longer history of diabetes, and exhibited more complications, including chronic kidney disease (CKD) and a higher BMI. The Gensini score was significantly higher in the elevated FBG group (95.88 ± 33.79 vs. 55.28 ± 18.59, p < 0.001). Elevated FBG was also associated with worse clinical outcomes, including higher rates of MACE, reinfarction, congestive heart failure (CHF), and cardiogenic shock. Elevated blood glucose levels, particularly fasting blood glucose (FBG), were associated with more severe CAD and poorer clinical outcomes in STEMI patients. These findings underscore the importance of early blood glucose control in improving outcomes and reperfusion success.